Interleaved Subwavelength Gratings Strip Waveguide Based TM Pass Polarizer on SOI Platform - Zhengying Xu; Tao Lyu; Xiaohan Sun (IEEE Photonics Journal, 2020)
We report on an ultra-compact, low loss and broadband TM-pass polarizer, which is constructed by two interleaved subwavelength-gratings (SWGs) waveguides inserted in the center of the strip waveguide on a silicon-on-insulator (SOI) platform. The device structure is optimally engineered to support Bloch mode for fundamental TM polarization only. Therefore, the TM mode transmits along the strip waveguide with rather low propagation loss while the TE mode is completely reflected by the embedded SWGs waveguides. Simulation results show that an efficient and ultra-compact TM-pass polarizer of 5.2 μm in length is realized with extinction ratio (ER) of 31.63 dB and insertion loss (IL) of 0.18 dB at the operating wavelength of 1550 nm. The operation bandwidth for ER over 20 dB and IL below 0.32 dB is 155 nm (from 1465 to 1620 nm). By increasing the period number, the ER performance and bandwidth can be further improved. Furthermore, the fabrication of the present polarizer only requires mono-lithography and single etch process, which will greatly reduce the fabrication difficulty.